Defining the future of bean production in Eastern Africa: Challenges, trends, and strategic priorities to 2050 - Mwungu, Chris; Petsakos, Athanasios; Andrade, Robert; Gotor, Elisabetta (2025)
Common beans (Phaseolus vulgaris) are central to food security, nutrition, and rural livelihoods in Eastern Africa, providing affordable protein and income to millions of smallholder farmers. While Uganda, Ethiopia, Rwanda, and Tanzania have made notable productivity gains, Kenya continues to face persistent structural constraints, and Burundi has experienced a long-term decline in productivity.